(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The grasshopper family Acrididae is one of the most diverse lineages within Orthoptera, including more than 6,700 valid species distributed worldwide. Grasshoppers are dominant herbivores, which have diversified into grassland, desert, semi-aquatic, alpine, and tropical forest habitats, and exhibit a wide array of morphological, ecological, and behavioral diversity. Nevertheless, the phylogeny of Acrididae as a whole has never been proposed. In this study, we present the first comprehensive phylogeny of Acrididae based on mitochondrial genomes and nuclear genes to test monophyly of the family and different subfamilies as well as to understand the evolutionary relationships among them. We recovered the monophyletic Acrididae and identified four major clades as well as several well- characterized subfamilies, but we also found that paraphyly is rampant across many subfamilies, highlighting the need for a taxonomic revision of the family. We found that Acrididae originated in the Paleocene of the Cenozoic period (59.3 million years ago) and, because the separation of South America and Africa predates the origin of the family, we hypothesize that the current cosmopolitan distribution of Acrididae was largely achieved by dispersal. We also inferred that the common ancestor of modern grasshoppers originated in South America, contrary to a popular belief that they originated in Africa, based on a biogeographical analysis. We estimate that there have been a number of colonization and recolonization events between the New World and the Old World throughout the diversification of Acrididae, and, thus, the current diversity in any given region is a reflection of this complex history.